2007
DOI: 10.1111/j.1464-410x.2007.06863.x
|View full text |Cite
|
Sign up to set email alerts
|

Interstitial laser coagulation in the management of lower urinary tract symptoms suggestive of bladder outlet obstruction from benign prostatic hyperplasia: long‐term follow‐up

Abstract: OBJECTIVETo evaluate the long-term effects, including durability, of interstitial laser coagulation (ILC) in patients with symptomatic benign prostatic hyperplasia. PATIENTS AND METHODSIn all, 49 men (median age 68 years, range 52-80) were treated with ILC; 22 men were assessed for a median (range) of 54 (46-61) months. Information on the timing and type of re-treatment were collected for the remaining patients. RESULTSThe median (quartiles) International Prostate Symptom Score decreased from 22 (19-28) at bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 22 publications
(26 reference statements)
0
13
0
1
Order By: Relevance
“…In addition, several studies have indicated that ILC often has effects on voiding variables and a high retreatment rate [11] . Laguna et al [24] reported that the retreatment rate was 15% in the first year following ILC, and further increased to about 40% 3 years after surgery, which was consistent with the study of Liedberg et al [29] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, several studies have indicated that ILC often has effects on voiding variables and a high retreatment rate [11] . Laguna et al [24] reported that the retreatment rate was 15% in the first year following ILC, and further increased to about 40% 3 years after surgery, which was consistent with the study of Liedberg et al [29] .…”
Section: Discussionmentioning
confidence: 99%
“…It is also a minimally invasive technique requiring regular TURP equipments and can relieve lower urinary tract obstruction and recover urinary function [11][12][13] .…”
Section: Introductionmentioning
confidence: 99%
“…Mean IPSS in our analysis decreased from 20 to 11.3 points and mean Qmax increased from 8.5 to 11.1 ml/sec during long term follow-up. Daehlin et al [9] reported a decrease of median IPSS from 22 to 13 points and an increase of Qmax from 8.6 to 10.2 ml/sec. Our patient cohort contains 37 patients who had a transurethral catheter preoperatively.…”
Section: Discussionmentioning
confidence: 99%
“…Taken into consideration the modest results of ILC presented in our analysis it seems difficult to support further use of this technique except in very selected patient groups [9,14]. Table 2: Cox proportional hazards analysis of predictive factors for treatment failure.…”
Section: Discussionmentioning
confidence: 99%
“…Several authors have concluded that this modality should probably be restricted to selected, high-risk patients. It can be safely performed with a combination of local anesthesia and intravenous sedation [Daehlin and Frugârd, 2007].…”
Section: Laser Applications In Urologymentioning
confidence: 99%